Nanostructured materials processing, properties and potential applications - Koch, C. C. (Noyes Pub./William Andrew Pub., 2002)
Nanostructured materials include atomic clusters, layered (lamellar) films, filamentary structures, and bulk nanostructured materials.
Keywords: Nanostructured materials.; elektronické knihy; electronic books